2018
DOI: 10.1093/biolre/ioy082
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effect of prematurely elevated progesterone in in vitro fertilization cycles: a literature review

Abstract: Premature progesterone (P) elevation was commonly seen in IVF prior to the utilization of GnRH analogues for suppression of endogenous gonadotropin release. The cause and effect of premature P elevation has finally been better elucidated in the past decade. Although still occurring in 5-38% of all IVF cycles, the adverse effects of premature P elevation on pregnancy outcomes are now well known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The authors of another recent study (Evans et al, 2018) found that in cycles affected by prematurely elevated P4 levels, vitrification of all embryos and performing a subsequent frozen embryo transfer yielded higher pregnancy rates. This was attributed to the detrimental effects of elevated P4 on the endometrium, resulting in endometrium-embryo asynchrony and implantation failure in fresh cycles.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of another recent study (Evans et al, 2018) found that in cycles affected by prematurely elevated P4 levels, vitrification of all embryos and performing a subsequent frozen embryo transfer yielded higher pregnancy rates. This was attributed to the detrimental effects of elevated P4 on the endometrium, resulting in endometrium-embryo asynchrony and implantation failure in fresh cycles.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, when serum P4 levels were > 1.75 ng/mL, the rates of GQE at the cleavage stage were significantly reduced. Some analyses have indicated that there is a significant association with a decreased probability of pregnancy during IVF cycles with detrimental endometrial receptivity under a serum P4 threshold > 1.5 ng/mL [ 17 , 18 , 19 ]. However, the clinical criteria for increased P4 levels are highly dependent on individual clinics [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is associated with the incidence of premature luteinization. 11,12 Premature luteinization is a term used to refer to a premature LH surge (LH surge), with serum progesterone levels being used as an indication of premature luteinization in various studies. 11,12…”
Section: Discussionmentioning
confidence: 99%
“…4,5 These three factors will be influenced by various characteristics of the patient, such as genetics, age, body mass index, and other comorbidities. 6 Ovarian reserve and the sensitivity of the follicular response to growth after COH are factors that strongly influence the oocyte maturation rate, and this condition can be reflected in the reproductive hormones levels of each participant in the ART program. This study aimed to determine which factors associated with oocyte maturation rate on ART participants.…”
Section: Introductionmentioning
confidence: 99%